Amelioration of Capecitabine Toxicity in Albino Rats Using Chrysanthemum Extract - Faheem, Jaklin L.; Abdou, Rania H.; Hanna, Pierre A.; Eltarabili, Reham M.; El-Hady, Kawther A. (Journal of Advanced Veterinary Research, 2024)
Cancer is a growing threat to human and animal health, The use of synthetic chemotherapy in the treatment of cancer is short because of lack of appropriate safety due to their drastic side effects. So, this study evaluated the ameliorative effect of Chrysanthemum on genotoxicity as well as renal and hepatic toxicity of Capecitabine (xeloda), as a model of anticancer drug. Thirty six male albino rat were divided into 6 groups. Serum samples were taken at 21 and 45 days and bone marrow samples at 45 days. Comet assay, biochemical tests for liver and kidney functions were done also serum oxidative biomarker were measured. The results of the present study revealed that capecitabine (xeloda) caused harmful genotoxic effect, biochemical changes in oxidative biomarkers, liver and kidney function, however the use of capecitabine (xeloda) in combination with Chrysanthemum ameliorated these changes especially with high dose. In conclusion, capecitabine adverse effects could be successfully alleviated through the co-administration of the natural antioxidant Chrysanthemum.Â